2021
DOI: 10.1371/journal.pone.0260316
|View full text |Cite
|
Sign up to set email alerts
|

Environmental safety evaluation of geopark based on CPTED concept and fuzzy comprehensive analysis

Abstract: In recent years, with the increasingly popular and openness of Geoparks, Environmental safety has become a major concern for sustainable geo-tourism. It is therefore necessary to conduct an environmental safety performance evaluation for promoting geo-tourism development. In order to identify and figure out the factors influencing the tourists’ environmental safety perception, an index system was established based on six principles of Crime Prevention Through environment design (CPTED) theory. A Questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…e authors conducted several experiments and the acquired outcomes indicate that the offered personalized recommendation system can effectively solve the problem of scarce tag data, and the recommendation performance of the trained recommendation system is significantly good. However, the accuracy of the personalized tourism recommendation algorithm is poor [5][6][7]. us, improving the efficiency, as well as, accuracy of such recommendation systems is the focus of this research.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…e authors conducted several experiments and the acquired outcomes indicate that the offered personalized recommendation system can effectively solve the problem of scarce tag data, and the recommendation performance of the trained recommendation system is significantly good. However, the accuracy of the personalized tourism recommendation algorithm is poor [5][6][7]. us, improving the efficiency, as well as, accuracy of such recommendation systems is the focus of this research.…”
Section: Related Workmentioning
confidence: 99%
“…e process continues to learn and obtain matrices P and Q through the random gradient descent method, and then predict score r ui . e user model not only considers the basic attributes of users, but also comprehensively considers the user project interaction information, and adds the factor of collective intelligence to the user model [7]. e user u is expressed in the characteristic matrix P as:…”
Section: User Personalized Travel Route Recommendationmentioning
confidence: 99%
See 2 more Smart Citations
“…Atlas, 2013;Armitage & Joyce, 2017;Armitage, 2016;Odufuwa, et al, 2019; have shown that, how a place is physically planned, designed, built, rebuilt, maintained, and managed contribute to its safety, security and vitality. Equally, Chen, et al, (2021) only focused on planning and design (Crime Prevention through Environmental Design [CPTED]) while neglecting other established dimensions such as communication and documentation, people (e.g. management) among others.…”
Section: Introductionmentioning
confidence: 99%